The Effect of the Global Method on Elementary Students’ Fable Reading and Viewing Skills Development - Nadilla, Nadilla; Ahmad, Mubarak (Lectura : Jurnal Pendidikan, 2025)
Early literacy development in primary education often encounters obstacles, particularly when students struggle to integrate text comprehension with visual and contextual language cues. The aim of this study is to examine the effectiveness of the Global Method in improving early literacy skills, specifically reading comprehension, visual interpretation, and contextual language understanding, among second-grade elementary students through the use of fable texts. Employing a quasi-experimental nonequivalent control group design, the study involved 64 students from a public elementary school in East Jakarta, divided into experimental and control groups. A 20-item multiple-choice literacy test, validated by experts, was administered before and after the intervention to measure reading comprehension, viewing skills, and mastery of language components such as nouns, adjectives, and antonyms. Results showed a significant improvement in the experimental group’s post-test scores (M = 87.97) compared to the control group (M = 68.59), with a significance value of 0.000 and a large effect size (Cohen’s d = 2.60), indicating strong practical relevance. The findings suggest that the Global Method not only improves academic performance but also promotes holistic literacy by integrating moral, visual, and linguistic competencies. Aligned with the Merdeka Curriculum’s principles of contextual and student-centered learning, this method presents a promising alternative for early literacy instruction. Future research should examine its adaptability across grade levels and explore digital enhancements for broader implementation.